ISO 9001 and Lean friends, not foes, for providing efficiency and customer value - Meyer, Douglas (Productivity Press, 2019)
ISO 9000 is a comprehensive set of international standards for quality management and quality assurance. These standards ensure that companies effectively document all aspects of their quality management to show transparency and efficiency within all processes. They are not industry specific and pertain to organizations of any size. Continuous improvement is a key facet of the ISO 9001 standard (the particular standard that specifies requirements for a quality management system), but it does not explain how to implement or maintain this improvement. Lean production methodologies surely provide this crucial and tactical information. Adding Lean production methodologies to quality management systems effectively focuses these improvement activities. In the long run, it will save companies much time and money. This book, written in the novel format, discusses the symbiotic relationship between ISO 9001 and Lean as both can be seamlessly integrated. It shows how Lean provides the process improvements that are required by the ISO 9001 quality management system - Lean is crucial for identifying and removing waste from your processes, which ultimately creates greater customer value. In addition, the book shows the crucial financial benefits of this integration. This novel clearly illustrates that these two systems can function effectively is one understands the complex balance of standardization and change. ISO 9001 is clearly controlled and audited while Lean is often empowering, less meticulously audited, and rarely controlled. While presenting interesting characters and interactions, this fictional story embeds real-life manufacturing speak with a message of the importance of successful synergy between Lean practitioners, production leaders, and quality departments